Model Optimization Design of Traction Pull Rod of Subway Structure Based on Finite Element Analysis - Wei WANG; Jianke ZHENG; Chunguang YAN; Xinghua SONG; Zhe XU (机车电传动)
Based on the finite element analysis software, the static strength of the three-dimensional model of a metro vehicle frame under abnormal working conditions was calculated. It was found that there were serious structural problems in the model of frame traction rod seat, which can not meet the requirements of the design. Based on the calculation results and design experience, the model was optimized. After optimization, the finite element analysis software was used again to recheck the calculation, and the test was carried out, which verified that the optimization scheme of the traction rod seat achieved the expected design effect.